NEW! Microsoft AZ-303 Certification Course Azure Architect Technologies - Colyer, Nick (Skylines Academy, LLC, 2020)
Welcome to Skylines Academy - home of the NEW AZ-303 Course! Since Microsoft announced the new AZ-303 Azure Architect Technologies exam, the Skylines Academy team has been hard at work to provide you with brand new and relevant content to help you pass the AZ-303 exam. The AZ-303 exam is the updated version of the AZ-300 exam and includes a lot of new material. The exam will be available starting June 29, 2020 so you could be one of the first to get certified! After taking the AZ-303 exam, we recommend you take the AZ-304 course from Skylines Academy (coming soon!) and exam. Once you pass both exams, you will be and EXPERT and obtain the Microsoft Certified: Azure Solutions Architect Expert badge. This course follows the Microsoft Skills Measured curriculum for the AZ-303. Nick Colyer, Master Instructor and Co-Founder of Skylines Academy will lead you through this brand-new course, filled with in-depth content around AZ-303 Azure services. Nick's previous version of this course, AZ-300, has received an average of 4.72 starts from thousands of students from every corner of the globe Student Reviews for the Azure Architect Technologies Course by Nick Colyer: "This is a great site to learn and Nick is awesome instructor. Since I have started my Journey with Skylines with AZ-900 this is the Third course I have completed so far. I am now preparing my AZ-300 Exam and after that 301." "Two Words ... Just Awesome!!!" "All the information was concise and engaging. I like how there is a lecture followed by a demo right after. It really helps to reinforce the topic while it is fresh in the mind. Overall, my second course with Nick, and I am enjoying them. I passed the AZ-103 exam using Nick's course on here, and moving on to 300 and 301. Thanks a bunch!" Course Description: The AZ-303 course is intended for IT engineers and architects who have previous experience of Microsoft Azure. Since Azure services were released, there have been several additions and updates to the platform that will be explored in this course. In order for you to achieve success and pass the AZ-303 exam, this Skylines Academy course will guide you through a series of sections, lectures, demonstrations, and hands-on labs, alongside other helpful study material. We have got you covered! During this course, you will gain knowledge and hands-on experience of: Understand Azure Active Directory (AD) and Subscriptions Implement Virtual Networking Implement Virtual Machines for Windows and L ...